Interfaith Dialogue in Christian Norway: Enactment of Inclusive Religiosity as Civilized Behavior - Liebmann, Louise Lund (Journal of religion in Europe, 2017)
Despite sparse scholarly attention from non-activists, Scandinavian interfaith fora are gaining momentum as a response to societal transformations of increased migration, world conflicts, and politically motivated violence. Combining theories of interaction, ritual performance, and civilizing processes, the article conducts a case study of public interfaith meetings held by a local interfaith forum in Kristiansand in Norway. Analyzing the meetings as organized cultural encounters, the study explores the transformative aspects of the events and it points to how the enactment of civilized forms of cross-cultural religiosity created within and by these public interfaith meetings is interlinked with formations of citizenship.